ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MODERASI (Studi pada Konsumen CS Kopi Tubruk Surakarta) - Febri Kumalaningrum, Erni Widajanti & Sutarno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
This study aims to analyze (1) the effect of service quality on customer loyalty CS Kopi Tubruk Surakarta. (2) the effect of customer satisfaction on consumer loyalty CS Kopi Tubruk Surakarta. (3) the effect of service quality on customer loyalty with customer satisfaction as a moderating variable. The study population was the whole kosumen CS Kopi Tubruk Surakarta with a sample of 115 respondents. Data collection techniques using questionnaires through the stages of testing the validity and reliability. Terms regression using classical assumption test. Data were analyzed using multiple linear regression and test of absolute difference. The conclusion of each hypothesis test results show that (1) Hypothesis 1, which states that "Service Quality significant effect on consumer loyalty CS Kopi Tubruk" unsubstantiated, the t test that generates a probability value 0.023 <0.05. (2) Hypothesis 2 stated that "consumer satisfaction have a significant effect on consumer loyalty CS Kopi Tubruk" unsubstantiated, the t test that generates a probability value 0.000 <0.05. (3) The third hypothesis which states that "consumer satisfaction moderate the effect of service quality on customer loyalty CS Kopi Tubruk" unsubstantiated, the t test that generates a probability value 0.000 <0.05. The conclusion from this study that the entire hypothesis can be accepted or proven true. Based on these results, maintaining customer loyalty is very important to improving service quality and customer satisfactionKeywords: service quality, customer satisfaction, customer loyalty